2011
DOI: 10.1103/physrevb.83.115121
|View full text |Cite
|
Sign up to set email alerts
|

Momentum-resolved electronic excitations in the Mott insulatorSr2IrO4studied by resonant inelastic x-ray scattering

Abstract: We report an Ir L 3 edge resonant inelastic x-ray scattering measurement of the low-lying electronic excitations in Sr 2 IrO 4 over the complete Brillouin zone of the IrO 2 plane. A remarkably strong inelastic signal which exceeds the elastic scattering in intensity is observed. Peaks observed at 0.5, 3.2, and 6.0 eV are respectively ascribed to an interband transition across the Mott gap and charge-transfer excitations from the O 2p band to the Ir 5d bands. The dispersion of the Mott gap excitation is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
75
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 25 publications
10
75
0
Order By: Relevance
“…In these materials, along with moderate electron correlations [6,7], there exists a strong relativistic spin-orbit coupling (SOC), which splits t 2g orbitals, already separated from e g orbitals due to a large crystal field, into the effective total angular momentum j = 1/2 doublet and j = 3/2 quartet orbitals in the atomic limit [8]. Since there are nominally five 5d electrons per Ir ion, the j = 1/2 orbital is half filled while the j = 3/2 orbitals are fully occupied.As opposed to simple expectation from strongly correlated 3d and 4d transition metal oxides [9][10][11][12][13], the experiments have revealed that the ground state of these Ir oxides is a j = 1/2 antiferromagnetic (AF) insulator [14][15][16][17]. The theoretical understanding of the j = 1/2 AF insulator has been also reported [14,[18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In these materials, along with moderate electron correlations [6,7], there exists a strong relativistic spin-orbit coupling (SOC), which splits t 2g orbitals, already separated from e g orbitals due to a large crystal field, into the effective total angular momentum j = 1/2 doublet and j = 3/2 quartet orbitals in the atomic limit [8]. Since there are nominally five 5d electrons per Ir ion, the j = 1/2 orbital is half filled while the j = 3/2 orbitals are fully occupied.As opposed to simple expectation from strongly correlated 3d and 4d transition metal oxides [9][10][11][12][13], the experiments have revealed that the ground state of these Ir oxides is a j = 1/2 antiferromagnetic (AF) insulator [14][15][16][17]. The theoretical understanding of the j = 1/2 AF insulator has been also reported [14,[18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…As opposed to simple expectation from strongly correlated 3d and 4d transition metal oxides [9][10][11][12][13], the experiments have revealed that the ground state of these Ir oxides is a j = 1/2 antiferromagnetic (AF) insulator [14][15][16][17]. The theoretical understanding of the j = 1/2 AF insulator has been also reported [14,[18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…6 These systems are also interesting because the role of spin-orbit coupling in the electronic structure is not completely clear, in particular it has been under debate what causes the insulating behavior in Sr 2 IrO 4 , whether the system is a Mott or a Slater insulator. [7][8][9][10][11][12] One of the keys to answer this question is to describe the electronic state the one t 2g hole is in. This has been described as a pure j ef f = 1/2 state 8, 13 or as a mixture due to contributions from both j ef f = 3/2 and e g states.…”
Section: Introductionmentioning
confidence: 99%
“…Previous RIXS studies [40][41][42][43] have identified peak D as a crystal-field excitation between the Ir 5d t 2g and e g orbitals, possibly mixed with a small amount (5%) of charge-transfer excitation from the oxygen 2p ligands [44]. In a nearly cubic crystal field, peak C is the spin-orbit exciton related to transition between the J eff =1/2 and 3/2 states [35,41,45].…”
mentioning
confidence: 99%